2000
DOI: 10.1007/bf03343778
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor polymorphisms and mutations in male infertility

Abstract: Normal spermatogenesis depends on a sequential cascade of genetic events triggered by factors encoded by sex chromosomes. To determine the contribution of genetic aberrations to male infertility, the X-linked androgen receptor (AR) gene was examined for mutations and polymorphisms in a large cohort of infertile men. Genetic screening of over 400 patients and controls showed that defects in the AR gene lead to the production of dysfunctional receptor protein in up to 10% of males with abnormally low sperm produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
1
21
0
2
Order By: Relevance
“…Mutation analysis must therefore be carried out directly by nucleotide sequence analysis. Specific point mutations associated with male infertility were found in the TAD and ABD region of the AR gene [138]. A M886V mutation found in 3 patients with severe oligozoospermia and a N727K mutation found in one patient both reduced the transactivation activity of the AR protein due to a reduced interaction with the TIF2 co-activator in the ABD region and the TAD region [138].…”
Section: Androgen Receptor Gene (Ar) Locusmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation analysis must therefore be carried out directly by nucleotide sequence analysis. Specific point mutations associated with male infertility were found in the TAD and ABD region of the AR gene [138]. A M886V mutation found in 3 patients with severe oligozoospermia and a N727K mutation found in one patient both reduced the transactivation activity of the AR protein due to a reduced interaction with the TIF2 co-activator in the ABD region and the TAD region [138].…”
Section: Androgen Receptor Gene (Ar) Locusmentioning
confidence: 99%
“…Specific point mutations associated with male infertility were found in the TAD and ABD region of the AR gene [138]. A M886V mutation found in 3 patients with severe oligozoospermia and a N727K mutation found in one patient both reduced the transactivation activity of the AR protein due to a reduced interaction with the TIF2 co-activator in the ABD region and the TAD region [138]. A clear therapeutic perspective for these patient´s infertility is given by administration of the androgen analogue, mesterolone [139].…”
Section: Androgen Receptor Gene (Ar) Locusmentioning
confidence: 99%
“…If GH acts as a ''cogonadotropin,'' it may be possible that differences in the GH/ insulin-like growth factor-1 axis could discriminate between men who suppress to azoospermia and those who do not. Finally, molecular approaches have demonstrated the importance androgen receptor polymorphisms play in male infertility (Yong et al, 2000). Differing polymorphisms of genes encoding for the androgen receptor, coactivators, or gonadotropin receptors could allow for continued intratesticular testosterone production or activity of testosterone or gonadotropins, thereby enabling spermatogenesis to persist.…”
mentioning
confidence: 99%
“…Therefore, attention was focused on the AR as a possible cause of the impaired spermatogenesis in subjects with idiopathic male infertility. It has long been postulated that defects in the AR gene can lead to partial or complete spermatogenic failure (Aiman et al 1979;Aiman and Griffin 1982) and more recently it has been shown that impaired function of the AR induces abnormalities in androgen action resulting in abnormal conditions such as androgen insensitivity syndrome (AIS) and infertility (Yong et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the observation that the elongation of CAG repeat in exon 1 of the AR gene causes pathogenesis of X-linked spinal and bulbar muscular atrophy (SBMA, or Kennedy's disease) strongly suggested that this region may play an important role in AR function (La Spada et al 1991;Belsham et al 1992). This hypothesis has extensively been investigated and a link between idiopathic male infertility and expansion of this polymorphic CAG tract in the AR gene has been suggested by several studies within the last Androgens are essential steroid hormones that determine the expression of the male phenotype (Yong et al 2000). Their actions are mediated by a single androgen receptor (AR) translocating to the nucleus upon binding to its ligand in order to regulate the expression of androgen-responsive genes.…”
mentioning
confidence: 99%